1992
DOI: 10.1007/bf00319366
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and function of capillary networks in subregions of the rat tuber cinereum

Abstract: The differentiated cytology, cytochemistry, and functions within subdivisions of the tuber cinereum prompted this morphometric and physiological investigation of capillaries in the medium eminence and arcuate nucleus of albino rats. Morphometric studies established that the external zone of the median eminence had 3-5 times the number and surface area of true and sinusoidal capillaries than the internal or subependymal median eminence zones, or either of two subdivisions examined in the arcuate nucleus. Type-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 38 publications
1
52
0
1
Order By: Relevance
“…However, an issue that must be taken into consideration is how leptin gains access to central feeding circuits protected behind the BBB. It has been suggested that leptin directly accesses the ARC through a leaky BBB; however, anatomical studies have clearly demonstrated that the ARC has an intact BBB as it does not contain type III fenestrated capillaries (45). Although a saturable blood-tobrain transport system for leptin has been demonstrated (2), it is not clear what concentrations of transported substances are delivered to their target normally protected by the BBB.…”
Section: Discussionmentioning
confidence: 99%
“…However, an issue that must be taken into consideration is how leptin gains access to central feeding circuits protected behind the BBB. It has been suggested that leptin directly accesses the ARC through a leaky BBB; however, anatomical studies have clearly demonstrated that the ARC has an intact BBB as it does not contain type III fenestrated capillaries (45). Although a saturable blood-tobrain transport system for leptin has been demonstrated (2), it is not clear what concentrations of transported substances are delivered to their target normally protected by the BBB.…”
Section: Discussionmentioning
confidence: 99%
“…The arcuate is characterized by receptors for peripherally active hormones, including ghrelin (Cowley et al, 2003;Mondal et al, 2005). It has been reported that the blood-brain barrier border could actually lie at the area between the median eminence and the distal part of the arcuate, indicating that the proximal arcuate could be exposed to circulating neuroactive substances (Shaver et al, 1992). Recently, a reciprocal linkage between the ventromedial arcuate to the SCN was established by means of anterograde and retrograde tracing techniques (Yi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Because the median eminence was labeled with 125 I-leptin, it is likely that leptin reaches the cells in the arcuate nucleus via the median eminence, a structure that belongs to the circumventricular organs, i.e., regions known to lack a BBB. Furthermore, there is evidence that the ventral but not the dorsal part of the arcuate nucleus lacks a BBB (Shaver et al, 1992). It is possible therefore that the leptin secreted exclusively from adipocytes is transported to the brain via the general circulation and acts on LR located in the ventromedial arcuate nucleus devoid of BBB.…”
Section: Discussionmentioning
confidence: 99%